Cell-penetrating peptide-doxorubicin conjugate loaded NGR-modified nanobubbles for ultrasound triggered drug delivery. (7th February 2016) - Lin, Wen; Xie, Xiangyang; Deng, Jianping; Liu, Hui; Chen, Ying; Fu, Xudong; Liu, Hong; Yang, Yang
Abstract: A new drug-targeting system for CD13 + tumors has been developed, based on ultrasound-sensitive nanobubbles (NBs) and cell-permeable peptides (CPPs). Here, the CPP-doxorubicin conjugate (CPP-DOX) was entrapped in the asparagine–glycine–arginine (NGR) peptide modified NB (CPP-DOX/NGR-NB) and the penetration of CPP-DOX was temporally masked; local ultrasound stimulation could trigger the CPP-DOX release from NB and activate its penetration. The CPP-DOX/NGR-NBs had particle sizes of about 200 nm and drug entrapment efficiency larger than 90%. In vitro release results showed that over 85% of the encapsulated DOX or CPP-DOX would release from NBs in the presence of ultrasound, while less than 1.5% of that (30 min) without ultrasound. Cell experiments showed the higher cellular CPP-DOX uptake of CPP-DOX/NGR-NB among the various NB formulations in Human fibrosarcoma cells (HT-1080, CD13 + ). The CPP-DOX/NGR-NB with ultrasound treatment exhibited an increased cytotoxic activity than the one without ultrasound. In nude mice xenograft of HT-1080 cells, CPP-DOX/NGR-NB with ultrasound showed a higher tumor inhibition effect (3.1% of T/C%, day 24), longer median survival time (50 days) and excellent body safety compared with the normal DOX injection group. These results indicate that the constructed vesicle would be a promising drug delivery system for specific cancer treatment.